Academic Capitalism And Historically Black Colleges And Universities: Institutional Conflict - Billy R. Brocato (Journal of Public and Professional Sociology)
The relevance of historically Black colleges and universities (HBCUs) in the current educational climate remain a critical issue. A mixed-methods case study was used to examine the conflicting concerns among faculty at a private HBCU in northeast Texas that has in recent years faced financial distress, declining enrollment, and administrative leadership turnover. The research design incorporated a two-step, critical race process that examined ‘faculty concerns’ on two hypothesized dimensions: academic capitalism versus academic autonomy. Relying on the meta-theory of institutional logics, the study examined the embedded racial structure of market-based metrics associated with HBCU faculty caught in a wave of ‘academic capitalism’ and the consequent paradox of trying to maintain their traditional role as scholastic gatekeepers. The findings suggest two institutional logics—neoliberalism at the administrative level and faculty autonomy at the academic level—were in conflict. It is recommend that HBCU stakeholders recognize the differences in institutional logics affecting faculty perceptions to mitigate the ongoing crises associated with administrators, finances, accreditation, and academic standards. Limitations and future directions for research are discussed.